Pharmacotherapy for the prevention of malaria in pregnant women: currently available drugs and challenges - Moore, Brioni; Davis, T. (2018)
© 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group. Introduction: Malaria in pregnancy continues to be a significant public health burden globally, with over 100 million women at risk each year. Sulfadoxine-pyrimethamine (SP) is the only antimalarial recommended for intermittent preventive therapy in pregnancy (IPTp) but increasing parasite resistance threatens its viability. There are few other available antimalarial therapies that currently have sufficient evidence of tolerability, safety, and efficacy to replace SP. Areas covered: Novel antimalarial combinations are under investigation for potential use as chemoprophylaxis and in IPTp regimens. The present review summarizes currently available therapies, emerging candidate combination therapies, and the potential challenges to integrating these into mainstream policy. Expert opinion: Alternative drugs or combination therapies to SP for IPTp are desperately required. Dihydroartemisinin-piperaquine and azithromycin-based combinations are showing great promise as potential candidates for IPTp but pharmacokinetic data suggest that dose modification may be required to ensure adequate prophylactic efficacy. If a suitable candidate regimen is not identified in the near future, the success of chemopreventive strategies such as IPTp may be in jeopardy.